PENGARUH PAJAK BARANG DAN JASA TERTENTU (PBJT) DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN KEPULAUAN SELAYAR TAHUN 2021-2025 - Amelia Safitri, Putri; Arman, Andi; Adziem, Faidul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes the influence of the Specific Goods and Services Tax (PBJT) and Regional Levies on the Locally-Generated Revenue (PAD) of Kepulauan Selayar Regency for the 2021-2025 period. The research is motivated by the regency's substantial tourism potential, most notably Takabonerate National Park, which has not been matched by optimal tax and levy revenue realization, leaving tourism potential and its contribution to regional fiscal independence disconnected. A quantitative descriptive approach was applied to secondary time-series data for 2021-2025 sourced from the Regional Financial and Asset Management Agency (BPKAD), the Regional Revenue Agency (BAPENDA), and the Central Statistics Agency (BPS) of Kepulauan Selayar Regency. Data were analyzed through classical assumption tests, multiple linear regression, and hypothesis testing (t-test and F-test) using IBM SPSS Statistics 29. The results show that PBJT (sig. = 0.002) and regional levies (sig. = 0.031) each have a positive and significant effect on PAD, while simultaneously the two variables significantly affect PAD (F = 331.985, sig. = 0.003) and explain 99.7 percent of its variation (R Square = 0.997). Optimizing the collection of PBJT and regional levies is therefore a key strategy for strengthening the fiscal independence of Kepulauan Selayar Regency.